Extremely Low Frequency Magnetic Fields Do Not Affect LTP-Like Plasticity in Healthy Humans - Capone, Fioravante; Pellegrino, Giovanni; Motolese, Francesco; Rossi, Mariagrazia; Musumeci, Gabriella; Di Lazzaro, Vincenzo (Frontiers in Human Neuroscience, 2020)
Introduction Several studies explored the biological effects of extremely low-frequency magnetic fields (ELF-MFs) in vitro, reporting the induction of functional changes in neuronal activity. In particular, ELF-MFs can influence synaptic plasticity both in vitro and in animal models but some studies reported an increase in long-term potentiation (LTP) whereas others suggested its reduction. However, no specific study has investigated such effect on humans. Aims To evaluate whether ELF-MFs affect the propensity of the human cortex to undergo LTP-like plasticity. Methods We designed a randomized, single-blind, sham-controlled, cross-over study on 10 healthy subjects. Cortical plasticity was induced by intermittent theta burst stimulation (iTBS) before and after 45-min ELF-MFs (75 Hz; 1.8 mT) or sham exposure and was estimated by measuring the changes of motor evoked potentials (MEP) amplitude before and after each iTBS. Results No adverse events were reported. No significant effects of ELF-MFs on cortical plasticity were found. Conclusion Whole-brain exposure to ELF-MFs (75 Hz; 1.8 mT) is safe and does not seem to significantly affect LTP-like plasticity in human motor cortex.